2015
DOI: 10.1016/j.redox.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between cyclooxygenase-2 and p53 in response to an endogenous electrophile

Abstract: Cyclooxygenase-2 (Cox-2) is rapidly expressed by various stimuli and plays a key role in conversion of free arachidonic acid to prostaglandins. We have previously identified 4-hydroxy-2-nonenal (HNE), a lipid peroxidation-derived electrophile, as the potent Cox-2 inducer in rat epithelial RL34 cells and revealed that the HNE-induced Cox-2 expression resulted from the stabilization of Cox-2 mRNA that is mediated by the p38 mitogen-activated protein kinase signaling pathway. In the present study, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…In hypertensive patients, the levels of IL-1␤ and IL-18 are elevated (40,52), and studies have shown that blocking the actions of inflammatory mediators results in amelioration of hypertension parameters (39). We verified that the treatment with captopril was able to decrease the expression of IL-1␤ after 24 h, with JNK the main kinase implicated in this gene modulation (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…In hypertensive patients, the levels of IL-1␤ and IL-18 are elevated (40,52), and studies have shown that blocking the actions of inflammatory mediators results in amelioration of hypertension parameters (39). We verified that the treatment with captopril was able to decrease the expression of IL-1␤ after 24 h, with JNK the main kinase implicated in this gene modulation (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Tumour protein p53 also plays a critical role in apoptosis (118). Stress signals such as DNA damage can enhance the otherwise low content of p53, which, in turn, increases the levels of the apoptotic gene (COX2) normally expressed in the brain (119,120). This has been confirmed by Galal et al (25), who reported that deltamethrin increased the mRNA expression of p53 and COX2.…”
Section: Apoptosismentioning
confidence: 86%
“…4-HNE has also been suggested to be involved in human pathologies since it is considered a key molecule in inflammation-related cell signaling [ 34 ]. It has been shown that under inflammatory conditions, the increased 4-HNE level leads to the upregulation of COX-2 and the initiation of the prostaglandin-dependent signaling pathways [ 35 ]. In this study, the activities of COX-1 and COX-2 were significantly elevated in the plasma of recovered COVID-19 patients in comparison to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%